The 'Alids The First Family of Islam, 750-1200 - Bernheimer, Teresa (Edinburgh University Press, 2022)
The first social history of the descendants of the Prophet Muhammad in early IslamGBS_insertPreviewButtonPopup(['ISBN:9780748638475','ISBN:9780748638482','ISBN:9780748682959']);This first in-depth study of the 'Alids focuses on the crucial formative period from the Abbasid Revolution of 750 to the Saljuq period of 1100. Exploring their rise from both a religious point of view and as a social phenomenon, Bernheimer investigates how they attained and extended the family's status over the centuries.The 'Alids are the descendants of the Prophet Muhammad, the elite family of Islam. The respect and veneration they are accorded is unparalleled in Islamic society, regardless of political or religious affiliation. And they have played a major role Islamic history, from famous early rebels to the founders and eponyms of major Islamic sects, and from 9th-century Moroccan and 10th-century Egyptian rulers to the current King of Jordan, the Ayatollah Khomeini and the Aga Khan.Key FeaturesIn-depth exploration of the distinction between Shi'ites and 'Alids: opens new possibilities for the understanding of the sectarian differences between Sunnis and Shi'itesBased on a wide range of primary sources in both Arabic and PersianDraws on historical, legal and biographical materialCritically examines recently published genealogical works on the 'Alid family